The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1103/physreve.79.036307
|View full text |Cite
|
Sign up to set email alerts
|

Maximum size of drops levitated by an air cushion

Abstract: Liquid drops can be kept from touching a plane solid surface by a gas stream entering from underneath, as it is observed for water drops on a heated plate, kept aloft by a stream of water vapor. We investigate the limit of small flow rates, for which the size of the gap between the drop and the substrate becomes very small. Above a critical drop radius no stationary drops can exist, below the critical radius two solutions coexist. However, only the solution with the smaller gap width is stable, the other is un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
115
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 28 publications
24
115
0
Order By: Relevance
“…Recently [11], it was demonstrated that drops can rebound after impact on an extremely cold solid carbon dioxide surface (at -79°C, well below the limit of even homogeneous nucleation of water), because of the formation of a sublimated vapor layer acting both as impact cushion and thermal insulator, enabling drops to hover and rebound without freezing. A sublimating surface is different from aerodynamically assisted surface levitation [23][24][25] and from the Leidenfrost effect [12][13][14][26][27][28], in the sense that it is independent from liquid properties, such as boiling temperature, and there is no loss of drop mass due to its own boiling (as in the Leidenfrost phenomenon). Of course, in both cases an intervening layer is generated between the drop and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently [11], it was demonstrated that drops can rebound after impact on an extremely cold solid carbon dioxide surface (at -79°C, well below the limit of even homogeneous nucleation of water), because of the formation of a sublimated vapor layer acting both as impact cushion and thermal insulator, enabling drops to hover and rebound without freezing. A sublimating surface is different from aerodynamically assisted surface levitation [23][24][25] and from the Leidenfrost effect [12][13][14][26][27][28], in the sense that it is independent from liquid properties, such as boiling temperature, and there is no loss of drop mass due to its own boiling (as in the Leidenfrost phenomenon). Of course, in both cases an intervening layer is generated between the drop and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…When theoretically deriving T L , one needs to determine the vapor thickness profile. In the case of a gently deposited droplet, this can be accomplished since the shape of the droplet is fixed except for the bottom surface, which reduces the problem to a lubrication flow of vapor in the gap between the substrate and the free surface [15][16][17][18][19][20]. For impacting droplets on an unheated surface at high Weber number We ≡ ρU 2 D 0 =σ (here, D 0 is the equivalent diameter of the droplet and ρ and σ are the density and the surface tension of the liquid, respectively), it is known that the neck around the dimple beneath the impacting droplet rams the surface.…”
mentioning
confidence: 99%
“…The pressure balance at the liquid/solid interface is changed, thus imposing respective mobility variations, and found applications in wetting control upon impingement [19] and in valving inside open-channel fluidics [20]. The presence and conservation of gas pockets resided in the solid-liquid interface and the significance of pressure gradient below and over the liquid phase has been highlighted, also in other studies [21][22][23].…”
Section: Introductionmentioning
confidence: 90%